Sustainable Tourism Research in India : A Review Study - Shekhar; Singh, Poonam; Shekhar, Sanket (Prabandhan: Indian Journal of Management, 2023)
Purpose : Sustainable tourism (ST) has been a buzzword in the tourism industry globally. In the Indian context, the theme has been rigorously researched, uncovering various theoretical and practical aspects. However, the strategists find themselves overwhelmed with the recommendations of researchers, which limit their efficiency in formulating plans. The study aimed to map the evolution of research on sustainable tourism in India and suggested future research actions and practical implications for managers. Methodology : The study applied SPAR-4-SLR, a scientific research protocol, to identify the 56 articles published in the Web of Science (WoS)-indexed journals. The study then used Science of Science (Sci2) and Gephi to conduct descriptive and network analyses, such as bibliographic coupling, keyword co-occurrences, and co-authorship analysis. Findings : The findings revealed that ST research in India revolved around managing the impact of tourism on the environment, developing economic avenues for sustainable tourism, balancing environment conservation and development, and understanding communities’ perceptions and eco-tourism. The results further highlighted a lack of empirical research linking SDG attainment to tourism sustainability. Practical Implications : The study will help researchers focus more on identifying the interlinkages between the SDGs that could be attained through sustainable tourism. Industry practitioners could benefit by identifying the knowledge gap in the theory and practice of effective strategy development. Originality : The study is one of a kind in using bibliometrics to study the themes in ST research in India and suggests future research areas post-pandemic that would assist researchers and policymakers.